2021
DOI: 10.2967/jnumed.121.261906
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Sink Effect in 68Ga-PSMA-11 PET: Myth or Reality?

Abstract: Background:We aimed to systematically determine the impact of tumor burden on the 68 Ga-prostate-specific membrane antigen-11 ( 68 Ga-PSMA) PET biodistribution by the use of quantitative measurements.Methods: This international multicenter retrospective analysis included 406 men with prostate cancer who received 68 Ga-PSMA PET/CT. Of these, 356 had positive findings and were stratified by quintiles into very low (Q1, ≤25 ml), low (Q2, 25-189 ml), moderate (Q3, 189-532 ml), high (Q4, 532-1355 ml) and very high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 26 publications
8
53
1
Order By: Relevance
“…Previous studies demonstrated an inverse correlation between PET-derived renal cortical uptake and PET-derived PSMA-TV. 26 In line with those findings, we also detected a tumor sink effect in our study (r = −0.35; p = 0.017). Interestingly, Violet et al have already reported on a reduced renal absorbed dose under Lu-177-PSMA-RLT in patients with increased TV, most likely due to a tumor sink effect under RLT.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies demonstrated an inverse correlation between PET-derived renal cortical uptake and PET-derived PSMA-TV. 26 In line with those findings, we also detected a tumor sink effect in our study (r = −0.35; p = 0.017). Interestingly, Violet et al have already reported on a reduced renal absorbed dose under Lu-177-PSMA-RLT in patients with increased TV, most likely due to a tumor sink effect under RLT.…”
Section: Discussionsupporting
confidence: 92%
“…24 Of note, recent studies also reported on a reduced renal cortical uptake in patients with higher tumor volume (TV) on both pretherapeutic 68 Ga-PSMA-11 PET/CT and renal dosimetry during Lu-177-PSMA-RLT. 25,26 However, the relative usefulness of these parameters for the prediction of treatment-related nephrotoxicity is poorly understood. In the present study, we aimed to evaluate the predictive performance of eGFR (obtained from blood samples), pretherapeutic Tc-99m-MAG3 clearance and PSMA-ligand PET-derived renal cortical uptake and TV for the occurrence of treatment-related CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Although treatment planning and dose application for RLT are generally recommended by regulatory agencies or scientific societies, no practical solution is available at the moment. Tumor sink effect in 68 Ga-PSMA-11 PET imaging was demonstrated previously [29]. These results suggest that candidates for PSMA-RLT with high tumor volume on pretherapeutic PSMA PET might benefit from increased therapeutic activity without exceeding the radiation dose limit for organs at risk.…”
Section: Discussionsupporting
confidence: 70%
“…However, given the small patient sample in our study, we could not address this aspect in our study and additional data are needed to investigate this issue. The observed non-significant but measurable increase in renal AD with increasing number of therapy cycles might be caused by the tumor sink effect as discussed in the literature [56][57][58][59], which is characterized by an increased absorbed dose to the kidneys due to a decreased tumor volume. However, since we did not systematically assess the total tumor volume (TTV) and its therapy-related changes in our study, we have to stick to a purely descriptive characterization at this point.…”
Section: Discussionmentioning
confidence: 92%